PRC’s Public Diplomacy Practice in Central Asia: Current Situation, Challenges and Prospects - Yufei Wang (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Central Asian region, with its rich reserves of energy resources and unique geopolitical position, is of particular importance for the modern foreign policy strategy of the People’s Republic of China. At the same time, the PRC’s public diplomacy and soft power in the Central Asian republics remain relatively understudied, despite the overall emphasis given to these issues by the Chinese researchers. It is this gap that this paper is partly intended to fill. The first section of the paper examines the evolution of the discourse on ‘public diplomacy’ in China and its perception in the Chinese academic community. The second section identifies the reasons for mainstreaming public diplomacy agenda in China’s foreign policy towards the Central Asian countries in recent years. The author shows that enhancement of economic and political cooperation between China and regional countries was not matched by a concurrent improvement of the China’s public image, on the contrary there has been a noticeable rise in Sinophobia. It was against this background that the PRC turned its attention to the use of public diplomacy tools as it launched the Belt and Road Initiative. The third section outlines the main thrusts of the Chinese public diplomacy in the region, including PR-diplomacy, media-diplomacy and humanitarian diplomacy. The final section identifies both the endogenous and exogenous challenges faced by the PRC’s public diplomacy in the Central Asian countries. The author argues that the competitiveness and effectiveness of China’s public diplomacy could be increased through expanding cooperation in the humanitarian sphere, implementation of digital technologies and media 2.0, as well as by increased engagement of non-governmental commercial and non-profit actors in interaction with the regional public. Either way, the author concludes that the Central Asian region will play an increasing role in the Chinese public diplomacy.